2020
DOI: 10.1038/s42003-020-01180-0
|View full text |Cite
|
Sign up to set email alerts
|

A spatial regime shift from predator to prey dominance in a large coastal ecosystem

Abstract: Regime shifts in ecosystem structure and processes are typically studied from a temporal perspective. Yet, theory predicts that in large ecosystems with environmental gradients, shifts should start locally and gradually spread through space. Here we empirically document a spatially propagating shift in the trophic structure of a large aquatic ecosystem, from dominance of large predatory fish (perch, pike) to the small prey fish, the three-spined stickleback. Fish surveys in 486 shallow bays along the 1200 km w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 69 publications
3
82
1
3
Order By: Relevance
“…It has been proposed that either competition for pelagic zooplankton resources such as Daphnia -that have declined in abundance with the re-oligotrophication of Lake Constance (Straile and Geller, 1998;Stich and Brinker, 2010;Rösch et al, 2017) -or direct predation on whitefish eggs and larvae (Roch et al, 2018;Ros et al, 2019) are responsible for this reduction in yield. Predation by sticklebacks on eggs and juveniles of their own species occurs frequently (Whoriskey and FitzGerald, 1985;Hyatt and Ringler, 1989;Smith and Reay, 1991;Foster and Bell, 1994;Manica, 2002;Mehlis et al, 2010) along with predation on larvae of other fish species (Hynes, 1950;Manzer, 1976;Delbeek and Williams, 1988;Kean-Howie et al, 1988;Gotceitas and Brown, 1993;Nilsson, 2006;Kotterba et al, 2014;Byström et al, 2015), while previous studies on stickleback populations in the Baltic Sea have suggested that intraguild predation on eggs and juvenile fish is responsible for the observed declines in perch (Perca fluviatilis, Linnaeus, 1758) and pike (Esox lucius, Linnaeus, 1758) recruitment (Nilsson, 2006;Bergström et al, 2015;Byström et al, 2015;Nilsson et al, 2019;Eklöf et al, 2020). It is possible that the same is occurring with Lake Constance whitefish populations, although evidence for this is currently lacking.…”
Section: Examining the Lake Constance Stickleback Population From A Gmentioning
confidence: 99%
“…It has been proposed that either competition for pelagic zooplankton resources such as Daphnia -that have declined in abundance with the re-oligotrophication of Lake Constance (Straile and Geller, 1998;Stich and Brinker, 2010;Rösch et al, 2017) -or direct predation on whitefish eggs and larvae (Roch et al, 2018;Ros et al, 2019) are responsible for this reduction in yield. Predation by sticklebacks on eggs and juveniles of their own species occurs frequently (Whoriskey and FitzGerald, 1985;Hyatt and Ringler, 1989;Smith and Reay, 1991;Foster and Bell, 1994;Manica, 2002;Mehlis et al, 2010) along with predation on larvae of other fish species (Hynes, 1950;Manzer, 1976;Delbeek and Williams, 1988;Kean-Howie et al, 1988;Gotceitas and Brown, 1993;Nilsson, 2006;Kotterba et al, 2014;Byström et al, 2015), while previous studies on stickleback populations in the Baltic Sea have suggested that intraguild predation on eggs and juvenile fish is responsible for the observed declines in perch (Perca fluviatilis, Linnaeus, 1758) and pike (Esox lucius, Linnaeus, 1758) recruitment (Nilsson, 2006;Bergström et al, 2015;Byström et al, 2015;Nilsson et al, 2019;Eklöf et al, 2020). It is possible that the same is occurring with Lake Constance whitefish populations, although evidence for this is currently lacking.…”
Section: Examining the Lake Constance Stickleback Population From A Gmentioning
confidence: 99%
“…The three-spine stickleback ( Gasterosteus aculeatus ) is abundant in the northern hemisphere in freshwater, marine habitats, and brackish water, such as the Baltic Sea, where it has become very abundant (Eklöf et al 2020 ). Three-spine sticklebacks were caught in Vikhögs harbour 29-km north of Malmö City (55°36′21″ N 13°02′09″ E) on the Swedish west coast on February 25, 2017 and transported to the stickleback facility at Stockholm University within 48 h. The fish were caught using a landing net with small mesh size.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon occurred in the coastal zone of the Baltic Sea, where commercial and recreational catches targeted mainly larger predatory individuals such as perch (Perca fluviatilis L.), pikeperch (Sander lucioperca (L.)), and northern pike, and cormorant pressure caused decreases in predator abundance. This, in turn, permitted the three-spined stickleback (Gasterosteus aculeatus L.) population, which had previously been limited by predators, to increase almost fifty-fold in the coastal zone (Donadi et al 2017, Nilsson et al 2019, Eklöf et al 2020. Such a large three-spined stickleback population, in addition to other environmental and anthropogenic factors, led to changes in the trophic pyramid that resulted in frequent algal blooms, bottom vegetation degradation, and increased eutrophication (Eriksson et al 2009, Eriksson et al 2011, Eklöf et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, permitted the three-spined stickleback (Gasterosteus aculeatus L.) population, which had previously been limited by predators, to increase almost fifty-fold in the coastal zone (Donadi et al 2017, Nilsson et al 2019, Eklöf et al 2020. Such a large three-spined stickleback population, in addition to other environmental and anthropogenic factors, led to changes in the trophic pyramid that resulted in frequent algal blooms, bottom vegetation degradation, and increased eutrophication (Eriksson et al 2009, Eriksson et al 2011, Eklöf et al 2020.…”
Section: Introductionmentioning
confidence: 99%